Have You Touched? A Case Study of Touch N Go E-Wallet - Daisy Mui Hung Kee; An Long Ow; Zhe Jian Ooi; Pavithara Sathiaseelan; Kuan Pang; Sathyan KA; Sahana Madhan (AIBPM Publisher, 2022)
This paper examines the relationship between the product features, convenience, perceived trust, customer satisfaction, and intention to use the Touch' n go e-Wallet. In this research, we have sent a survey to our target respondents, the people who are using Touch' n go e-Wallet. They are include students, employed, unemployed, self-employed, and retired respondents, including all races from all age levels. In this research, we want to know whether the respondents would like to use cash to pay in their daily lives or prefer to transit the cash to cashless. A total of 150 respondents has participated in our online survey via Google Forms. Our research which is findings which product features, convenience, perceived trust, customer satisfaction will what effects to the intention to use of consumer towards the Touch’ N Go e-Wallet. Beside then that, our team also do some research towards the product features, convenience and perceived trust will affect the customer satisfaction or not. This research provides new insights and recommendation